Combinatorial effect of substratum properties on mesenchymal stem cell sheet engineering and subsequent multi-lineage differentiation. (1st September 2015) - Chuah, Yon Jin; Zhang, Ying; Wu, Yingnan; Menon, Nishanth V.; Goh, Ghim Hian; Lee, Ann Charlene; Chan, Vincent; Zhang, Yilei; Kang, Yuejun
Graphical abstract: Abstract: Cell sheet engineering has been exploited as an alternative approach in tissue regeneration and the use of stem cells to generate cell sheets has further showed its potential in stem cell-mediated tissue regeneration. There exist vast interests in developing strategies to enhance the formation of stem cell sheets for downstream applications. It has been proved that stem cells are sensitive to the biophysical cues of the microenvironment. Therefore we hypothesized that the combinatorial substratum properties could be tailored to modulate the development of cell sheet formation and further influence its multipotency. For validation, polydimethylsiloxane (PDMS) of different combinatorial substratum properties (including stiffness, roughness and wettability) were created, on which the human bone marrow derived mesenchymal stem cells (BMSCs) were cultured to form cell sheets with their multipotency evaluated after induced differentiation. The results showed that different combinatorial effects of these substratum properties were able to influence BMSC behavior such as adhesion, spreading and proliferation during cell sheet development. Collagen formation within the cell sheet was enhanced on substrates with lower stiffness, higher hydrophobicity and roughness, which further assisted the induced chondrogenesis and osteogenesis, respectively. These findings suggested that combinatorial substratum properties had profound effects on BMSC cell sheet integrity and multipotency, which had significant implications for future biomaterials and scaffold designs in the field of BMSC-mediated tissue regeneration.